Histopathologic evaluation of the peritoneum exposed to heat shock. Experimental study in rats - Lopes, João Vieira (2007)
PURPOSE: To evaluate histopathologic alterations of the peritoneum exposed to heat shock. METHODS: Sixty rats were randomly distributed into 6 groups: Heat Shock (HS), High Temperature (HT), Body Temperature (BT), Temperature 0oC (TZ), Sham (SH) and Control (CG) with 10 animals each. The peritoneal cavity of animals from groups HS, HT, BT and TZ was irrigated with NaCl solution 0.9% at temperatures 50ºC, 0ºC, 50ºC, 37ºC and 0ºC, respectively. For animals from group SH, the procedures were simulated and those from group CG, laparotomy and biopsies were conducted. Twenty-four hours later, biopsies of the peritoneum for exams under light and electronic microscopy were performed. RESULTS: Edema was found in groups HS 80%, HT 60%, BT 30% TZ 70%, SH 40% and CG 30%. Vascular congestion was found in groups HS 20%, HT 30%, BT 10% and TZ 20%. Erythrocyte extravasation was found in groups HT 60% and SH 10%. Mesothelium destruction was found in 100% of specimens from groups HS, HT, BT, TZ, SH and CG 90%. Necrosis was found in groups HS 30%, HT 20% and BT 10%. The mean peritoneal thickness ranged from 42.26 µm (TZ) to 26.42 µm (CG). CONCLUSION: The heat shock caused no deaths, but promoted significant peritoneal edema without affecting the other histopathologic indicatives. _______________________________________________________________________________ RESUMO